Single-Stage Vacuum Pressure Swing Adsorption for Producing High-Purity Oxygen from Air - Daniel Ferreira (2015)
The maximum oxygen concentration obtained using a conventional single-stage pressure swing adsorption unit isca. 95% balanced mostly with argon. However, there are several applications requiring simple and compact units for producinghigh-purity oxygen (≥99%), such as medical, military, or aerospace. This article studies a single-stage vacuum pressure swingadsorption (VPSA) unit, loaded with silver-based zeolite AgLiLSX, for producing ca. 1 LSTP·min−1 of high-purity oxygen. Theunit was designed on the basis of the experimental and simulation results obtained with a lab-scale unit. For a productconcentration of 99.0%, the recovery obtained was ca. 8.0% with a productivity of 9.0 m3·h−1·ton−1.